200°C/5 MHz GaN‐based gate driver circuits with 1 nF/4.7 Ω RC load for high‐temperature high‐frequency all‐GaN IC applications. Issue 22 (25th September 2020) - Xu, Zhe; Zhou, Yang; Xin, Xiong; Wang, Wenjie; Xie, Wuze; Li, Juntao
Abstract : A GaN‐based gate driver circuits have been successfully designed and fabricated using a commercially available 6‐inch GaN‐on‐Si platform. The driver circuits consist of three‐stage direct‐coupled FET logic (DCFL) inverters featuring monolithically integrated depletion‐mode (D‐mode) and enhancement‐mode (E‐mode) high electron mobility transistors (HEMTs). At room temperature (RT), at a supply voltage of 4 V the single‐stage DCFL fabricated on the same die exhibits a large gate swing (3.84 V) and large noise margins (logic‐low noise margin (NML ) of 1.55 V and logic‐high noise margin (NMH ) of 2.18 V), both of which are desirable for all‐GaN IC applications. Meanwhile, the gate driver circuits were characterised up to 200°C on a PCB with a capacitance load of 1 nF in series with 4.7 Ω resistance to resemble the load condition. At 200°C, the gate driver circuits function well even at 5 MHz operation frequency. The turn on/off propagation delay and rise/fall time of the gate driver circuits are 5/40 and 22/18 ns, respectively. As far as the authors' knowledge, this is the highest reported operation frequency for GaN‐based gate driver circuits under such high temperature, making it very promising for high‐temperature high‐frequency all‐GaN integrated circuit (IC) applications.